The importance of life cycle on the future development of tourist destination - Brankica Todorovic (CES Working Papers, 2019)
The development of national economies is related to environmental pressures which have negative consequences on the environment. The phase of the life cycle indicates the need to change access to the development of the destination, thus being a useful marketing tool, as well as, an instrument in the environmental protection policy. The work analyses the theoretical phases of the life cycle of touristic destinations and presents the results of the research Case study: Nature Park Zlatibor - the most visited touristic destination. The research aims to identify the phase of the life cycle in which the destination is currently located, according to the Batler model, and to measure the achievement of ecological and economic sustainability. Additionally, it explains the opposing relations between the economic interest and preserving the protected area.
Keywords: 330; life cycle; touristic destination; sustainable development